Effect of COVID-19 pandemic on epidemiology and antimicrobial susceptibility of Campylobacter sp., Salmonella enterica and Yersinia enterocolitica in Southwest Finland 2018-2022 - Orpana, Tanja (My University, 2025)
Purpose The purpose of this study was to monitor the antimicrobial susceptibility and epidemiology of fecal Campylobacter sp., Salmonella enterica and Yersinia enterocolitica strains collected from clinical samples in Southwest Finland. Methods Fecal samples were collected biannually from patients with ongoing symptoms of gastroenteritis from 2018 to 2022. Bacteria were isolated from PCR positive samples and tested for antimicrobial susceptibility according to EUCAST guidelines. Results A clear drop during 2020 in travel-associated and domestic enteric pathogens was detected. Antimicrobial resistance of the studied bacteria varied through the study period. C. jejuni antimicrobial resistance has been on average: ciprofloxacin 60%/89% and tetracycline 37%/68% for domestic (n=154) and travel-associated (n=11) strains, respectively. Erythromycin resistance was not detected. S. enterica antimicrobial resistance has been on average: ampicillin 52%/35%, ciprofloxacin 28%/36%, cefotaxime 6%/5% and co-trimoxazole 0%/13%, for domestic (n=25) and travel-associated (n=31) strains, respectively. One domestic and five travel-associated extended-spectrum beta-lactamase PCR positive strains were detected. In addition, one meropenem-resistant travel-associated strain was detected. For domestic Y. enterocolitica strains (n=64), antimicrobial resistance has been on average: co-trimoxazole 2%, ciprofloxacin 37%, cefotaxime 7%, ceftazidime 10%, and ceftriaxone 5%. No travel-associated isolates were reported. Conclusions This study shows that in between autumn 2019 and autumn 2020 there was a clear decrease in travel-associated isolates of Campylobacter sp. and S. enterica. Lockdowns due to COVID-19 pandemic decreased the number of diagnosed enteric pathogens and also reduced the emergence of resistant strains in Finland. Thus, our results confirm that travelling is the most important source of S. enterica infections in Finland.
Keywords: Antimicrobial resistance, AMR, enteropathogens, fecal samples, Campylobacter, Salmonella, Yersinia